Development and validation of the Global Post Trauma Symptom Scale-Uganda among trauma-affected adults - Lynn Murphy Michalopoulos; Melissa Meinhart; Erin Walton; David Robertson; Autumn Thompson; Thomas Northrup; Jong Sung Kim; Nikita Aggarwal; Anne Conway (European Journal of Psychotraumatology)
Background: Post-traumatic stress measurement in non-Western contexts often utilizes Western assessment tools.Objective: The purpose of this study was to adapt and validate the Global Post-Trauma Symptom-Item Bank (GPTS-IB) among adult caregivers of youth living with HIV in Uganda.Methods: We utilized qualitative and quantitative methods to establish validity and to develop a reduced version of the GPTS-IB.Results: Cognitive interview results (n = 31) indicated that participants understood items of the GPTS-IB, but revisions in wording were needed for some items. A reduced version of the GPTS-IB, the Global Post Trauma Symptom Scale-Uganda (GPTSS-U) was created through item response theory analyses based on discrimination criteria and difficulty parameters. A relationship between the GPTSS-U and the PHQ-9 (r = 0.547; p < .000) scores and the PCL-5 (r = 0.9, p < .001) scores indicated acceptable discriminant and convergent validity, respectively. Test information function curve findings indicated that the GPTSS-U was most precise at moderate to severe levels of post-traumatic symptoms. Using nested linear regression models, we found incremental or predictive validity as the total scores on the GPTSS-U significantly predicted functional impairment (p < .05) beyond the ability of the Post Traumatic Stress Checklist-5.Conclusions: Results indicated that the GPTSS-U was a valid measure of post-traumatic symptoms among caregivers of youth with HIV in Uganda. Future research should continue to assess the utility of the GPTSS-U in other non-Western contexts.